can someone explain this to me?

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions.

- anonymous

can someone explain this to me?

- katieb

See more answers at brainly.com

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- anonymous

are you trying to solve for m?

- anonymous

yes theres some options a. m = 4
b. m = 2
c. m = 6
d. m = -2

- anonymous

ok well here you should start by distributing the -4 so
-4*-3m = 12m and -4 *(-2) = 8 which means you now have 12m+8=32

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

you can subtract 8 from both sides like this 12m +8 -8 = 32 - 8

- anonymous

so now you have 12m=24 and now you can divide 12 from both sides

- anonymous

\[\frac{ 12m }{ 12 } = \frac{ 24 }{ 12 }\] leaving you with m = 24/12

- anonymous

which is 2

- anonymous

? i believe

- anonymous

it's like the circle question you did when you had to move the 2π around

- anonymous

yes

- anonymous

yeah i think they are all the same these just confuse me

- anonymous

once you get the hang of rules of algebra you'll have no issues with this stuff. :)

- anonymous

just always remember "What you do to one side of an equation you must do to the other side."

- anonymous

i hope! theres a couple like this do you mind?

- anonymous

cause i kind of get it but then when i'm left to do it alone I have no idea

- anonymous

go for it

- anonymous

What is the solution to -(-5 - 6x) = 4(5x + 3)?
Select one:
a. x = -2
b. x = -1/2
c. x = 2
d. x = 1/2

- anonymous

oh!! i remember dat one, x= -1/2, right teehee|dw:1444597877958:dw|

- anonymous

-(-5 - 6x) = 4(5x + 3)\[(-1)(-5-6x) = 5+6x \]\[ 4(5x +3) = 20x+12 \]
from here you now have 5+6x = 20x +12 you want to get all the x terms on one side and all the non x terms on the other
so it becomes 6x-20x = 12-5 which when combined is -14x = 7
now divide -14 from both sides and you'll have \[x = -\frac{ 7 }{14 }\]

- anonymous

simplify and you will have \[x = -\frac{ 1 }{ 2 }\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.